SCARS MAY INDEED “HAVE THE STRANGE POWER TO REMIND US THAT OUR PAST IS REAL”:* A PATIENT REPORTED OUTCOME MEASURES STUDY IN WOMEN WITH POSTMASTECTOMY BREAST RECONSTRUCTION - Ahmet Biçer; Erdem Güven; Çiğdem Derya Aytop; Burcu Çelet Özden; Hülya Aydın; Hayri Ömer Berköz (İstanbul Tıp Fakültesi Dergisi)
Objective: One of the leading causes of death among women is breast cancer. The disease process and treatment journey consume patients’ emotional and physical energy, severely affecting mood, self-esteem, body image, sexual functions, commitment, and overall quality of life. Postmastectomy breast reconstruction is known to revert some of these adversarial conditions. This study uses patient-reported outcome measures (PROMs) to investigate the factors influencing the end result and quality of life regarding postmastectomy breast reconstruction.Material and Method: Thirty-four patients who’d undergone breast reconstruction filled out a questionnaire form including 54 questions pertaining the patients’ surgical and oncological history, demographics, mood, self-esteem, body and breast self-image, social and familial support mechanisms, and satisfaction with life and reconstruction. The study then collected anthropometric measurements and standardized photographs and had plastic surgery residents assess aesthetic outcome with regard to the photographs. Result: Half of the patients had immediate while the other half had delayed reconstruction. Of the patients, 10 (29.4%) had reconstructions that only involved an implant, 15 (44.1%) had reconstructions that only involved autogenous tissue, and nine (26.5%) that had both. No significant association could be found for the reconstruction method or timing of the reconstruction with aesthetic results, symmetry, or patient satisfaction. Meanwhile, nipple-areolar complex (NAC) reconstruction contributed to significantly better aesthetic outcomes (p=0.026) and overall patient satisfaction (p=0.029). Scar issues were found to significantly affect satisfaction scores (p=0.008) while not affecting the aesthetic outcome. Conclusion: Neither symmetry nor aesthetic outcome were found to be major factors influencing patients’ overall satisfaction with breast reconstruction. However, scars are relevant as constant reminders of past surgeries. Another significant factor in patient satisfaction was NAC reconstruction.